Investigating mechanical and biological properties of additive manufactured Ti6Al4V lattice structures for orthopedic implants - Gurkan, Doruk; Sagbas, Binnur; Dalbayrak, Basak (Springer Heidelberg, 2023)
Titanium alloys are widely used for biomedical applications as porous lattice structures whose abilities can be altered via unit cell designs, pore size, and topology. In this study, Ti6Al4V octahedron, star, and dodecahedron cubic and plate lattice structures were designed as 0.20-mm strut diameter with different porosity values (83.06% for octahedron, 53.46% for star, and 63.29% for dodecahedron) and manufactured by laser powder bed fusion. Compression tests were conducted by ISO 13314. The elastic modulus for octahedron, star, and dodecahedron lattices were found 1.7 GPa, 8.6 GPa, and 6.7 GPa, respectively, and results were promising in terms of reducing stress shielding. Relation between relative density and mechanical response was investigated. Chitosan-substituted hydroxyapatite composite coating successfully deposited by electrophoretic deposition on surfaces for biological assessment. Coating increased bioactivity and reduced cell death, especially around implant samples. Chitosan addition ensured an antibacterial effect. Results revealed that mechanical properties and biological responses of structures were affected by the lattice design and pore size.
Keywords: Laser powder bed fusion; Lattice; Pore; Chitosan-hydroxyapatite composite coating; Compression test; Biocompatibility